PERHITUNGAN BREAK EVEN POINT PADA PERUSAHAAN MANUFAKTUR KAYU - Mutiara, Piala (Jurnal Sains dan Teknologi ISTP, 2024)
Nowadays, many companies calculate the costs that occur in a production process. But it is very rare for companies to calculate when a company will return on capital and when a company will experience a loss or profit. The purpose of calculating the Break Even Point (BEP) is to find out how many units are needed to return on capital or how much turnover must be achieved so that the company returns on capital. Data processing is carried out using the Break Even Point calculation method by collecting data in the form of fixed cost data and variable cost data for a production process. From the results of data processing, it is obtained that BEP = 994 units with a price of IDR 278,174,937. The company makes a profit if sales are above the BEP and conversely makes a loss if it is below the BEP.